Medición indirecta de la Serviciabilidad en las vías asfaltadas de segundo orden del cantón Guaranda - Lara Lara, David Joel (2023)
The aim of the present research is to drive “THE RESPONSIBILITY OF ROAD MAINTENANCE AND TRAFFIC MANAGEMENT” presenting us strategies how to repair the roads of our country, taking into consideration technical criteria to guarantee results such as: resurfacing, patching and reparing in the pavement, among others, using technician tools ; even though road users perceive these suggestions aren´t taken into account, they couldn´t contribute with a technical information. In the next research work, the technical road assistance will be able to make it , in the second class roads of Guaranda canton, using the PSI method and the Servqual model, in order to examine a similarity in the results of the technical method of the road user´s evaluation and perception. In the implementation of data collection, three techniques were taken into account; literature review on roads construction, merlin road roughness measurement . Due the results of the PSI method and the Servqual model were obtained, the Pearson coefficient was carried out, obtaining a strong positive linear correlation of 0.990, where it is explained that the variables are directly bond, after obtaining these results, a prediction model was taken into account four dimensions of the Servqual model with the IRI. In order to use the predict method, the range in which the structural equations are valid and reliable